2018
DOI: 10.1186/s13054-017-1927-3
|View full text |Cite|
|
Sign up to set email alerts
|

Tracheal intubation in critically ill patients: a comprehensive systematic review of randomized trials

Abstract: BackgroundWe performed a systematic review of randomized controlled studies evaluating any drug, technique or device aimed at improving the success rate or safety of tracheal intubation in the critically ill.MethodsWe searched PubMed, BioMed Central, Embase and the Cochrane Central Register of Clinical Trials and references of retrieved articles. Finally, pertinent reviews were also scanned to detect further studies until May 2017. The following inclusion criteria were considered: tracheal intubation in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 51 publications
(87 reference statements)
0
45
1
2
Order By: Relevance
“…Oxygen desaturation is the most common reason for aborted first attempt at intubation, both of which increase the risk of further life‐threatening adverse events. Inadequate resuscitation prior to intubation and failure to use strategies to mitigate physiological derangements prior to and during intubation may increase the risk of life‐threatening adverse events …”
Section: What Are the Contributors?mentioning
confidence: 99%
“…Oxygen desaturation is the most common reason for aborted first attempt at intubation, both of which increase the risk of further life‐threatening adverse events. Inadequate resuscitation prior to intubation and failure to use strategies to mitigate physiological derangements prior to and during intubation may increase the risk of life‐threatening adverse events …”
Section: What Are the Contributors?mentioning
confidence: 99%
“…Airway management is a commonly performed procedure in the ED and ICU, being tracheal intubation the gold standard. Several studies identify relatively high rates of complications in these settings, ranging from 20 to 31% in ICUs [1], which can be life-threatening, including severe hypoxia, hemodynamic collapse, cardiac arrest and death [2]. This pool of patients differs from those in elective surgery intubated in the operating room taking into account that they often present with severe respiratory failure, hemodynamic instability, absence of a fasting state and other comorbilities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies identify relatively high rates of complications in these settings, ranging from 20 to 31% in ICUs [1], which can be life-threatening, including severe hypoxia, hemodynamic collapse, cardiac arrest and death [2]. This pool of patients differs from those in elective surgery intubated in the operating room taking into account that they often present with severe respiratory failure, hemodynamic instability, absence of a fasting state and other comorbilities [2]. In general, hypoxemia is common in patients requiring intubation and care should be given to its quick performance to avoid aspiration [3] and further dessaturation, given that previous studies reported a significant increase in hypoxemia with the increase in laryngoscopic attempts [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended to include a cardiovascular component in the protocol during intubation of ICU patients, by defining volume responsiveness and early administration of vasopressors to prevent hemodynamic collapse. [14][15][16] Optimizing the hemodynamics prior to intubation is crucial to prevent cardiovascular complications in the periintubation period. The information obtained by performing a brief bedside cardiac ultrasound can change the management of critically ill patient, preventing potential decompensation during and following endotracheal intubation.…”
Section: Introductionmentioning
confidence: 99%